Evaluation of semen collected from commercial rams by electro-ejaculation - Lovatt, F.M.; Genever, L.; Glover, M.J.; Henry, J. (BMJ Publishing Group, 2016)
Annual ram pre-breeding soundness examinations (PBSE) are accepted as an integral component of veterinary flock health planning to identify rams not capable of achieving high conception rates. This preliminary study collected information from 280 rams presented to five veterinarians for routine PBSE on commercial farms in England in 2013. The study compared the outcome of a physical examination, which included palpation of external genitalia, with the gross and progressive motility of the semen produced by electro-ejaculation.